Ocena przydatności badania mfVEP w diagnostyce guzów przysadki mózgowej - Piekarska, Anna; Lubiński, Wojciech; Gosławski, Wojciech; Wieliczko, Wiesława; Syrenicz, Anhelli; Olszowski, Tomasz; Karczewicz, Danuta (Klinika Oczna / Acta Ophthalmologica Polonica, 2008)
Purpose: To evaluate the mfVEP test in detection of the optic nerve neuropathy in pituitary tumors. Material and methods: We examined 30 eyes of 15 patients with confirmed by MRI pituitary tumors (7 patients with macroadenomas and 8 patients with microadenomas). In all patients the routine ophthalmologic examination, multifocal visual evoked potentials (mfVEP) and standard static perimetry (central 24-2 threshold), were performed. The control group consisted of 30 eyes of 15 healthy persons. Results: In 53% (16/30) of eyes manifested changes in static perimetry and/or in mfVEP test. In 13% (4/30) of eyes abnormal static perimetry and mfVEP were simultaneously observed. The only mfVEP abnormalities were the most frequent feature and were observed in 30% (9/30) of eyes. Only abnormal static perimetry results were observed in 10% (3/10) of eyes. In those eyes in related areas of mfVEP recordings the mean peak-to-peak amplitude was significantly reduced compare to the control group. In mfVEP test statistically significant peak-to-peak amplitude reduction was observed in superotemporal quadrants in comparison to the control group (p < 0.009). Conclusions: MfVEP can be useful test in the optic nerve dysfunction/ neuropathy diagnosis in patients with pituitary tumors.